On the nature of Applied linguistics: theory nad practice relationships from a critical perspective (GIST – Education and Learning Research Journal, 2007)
On the Nature of Applied Linguistics: Theory and Practice Relationships from  a Critical Perspective This article explores the relationships between Applied Linguistics and other related di sciplines concerning language use and language teaching issues. It seeks to trace the changes in the view of the relationship between theory and practice in Applied Linguistics, to explain the reason for those changes, and to discuss the implications for language teaching. Some general assumptions that serve as a context for this are presented. It also shows possible forms of interaction between basic and applied science (linguistics in this case) and practical activities, and presents some implications to teacher education and theway these visions have permeated language education and foreign language teaching practices.